Recovery of consciousness after epileptic seizures in children. Issue 1 (4th July 2006) - Allen, J E; Ferrie, C D; Livingston, J H; Feltbower, R G
Abstract : Objective: To investigate the duration of postictal impairment of consciousness and the factors that affect it. Patients and methods: 90 children aged 1–16 years (37 male, 53 female, median age 6 years), attending the accident and emergency department, and inpatients of Leeds General Infirmary, Leeds, UK, who had experienced seizures involving impairment of consciousness. Interventions—hourly modified paediatric coma scores were determined, until a coma score of 15 was obtained. Linear regression analysis was used to determine the factors influencing recovery time. Results: 49 children were excluded owing to incomplete coma scoring, lost notes and refusal of consent. Median time for full recovery of consciousness was 38 min (0.63 h, range 0.05–17 h). Median recovery time was 18 min (0.3 h, range 0.05–9 h) from febrile seizures, which was significantly shorter than for seizures of other aetiologies (p<0.05), 1.35 h (range 0.07–13.13 h) from idiopathic seizures, 1.25 h (0.07–12.1 h) from remote symptomatic seizures and 4.57 h (0.25–17 h) from acute symptomatic seizures. Median recovery time after the use of benzodiazepines was 3.46 h (range 0.08–14.25 h), and was significantly longer (p<0.05) than for seizures not treated with benzodiazepines (median 0.47 h, range 0.05–17 h). Age, sex, seizure type and duration did not significantly affect recovery time. Conclusions: Most children experiencing febrile seizures recover within 30 min. An acute symptomatic aetiology should be considered if recovery takes >1 h.